Mucoepidermoid Carcinoma of Gingiva - Patchava, Mohanakrishna; Nugala, Babitha; Sindhura, N; Anupama, T (Journal of Orofacial Research, 2015)
Background: Neoplasms of minor salivary gland origin occur much less commonly than from major salivary glands. Only 57% of gingival tumors are neoplastic. Of the 57% gingival tumors, 2.5% are salivary gland in origin. Neoplasms of the minor salivary glands rarely involve the gingiva. Materials and methods: The clinicopathologic features of the mucoepidermoid carcinoma (MEC) in a female patient are described. A 39-year-old woman showed a slowly growing, painless, soft mass in the lower left mandibular gingiva. The whole lesion was excised and histopathologic analysis was performed. Results: The histopathologic sections showed a tumor composed of malignant cells with squamoid features admixed with few mucous cells suggestive of MEC. The healing after tumor removal was uneventful. Conclusion: This case report highlights the importance of histopathological study of even a small apparently benign looking gingival lesions in anamnestically healthy patients in the oral cavity to verify existence of much more than that which meets our eye, so that appropriate, timely treatment canbe rendered.